Mixed Botryoid and Spindle Cell Bladder Rhabdomyosarcoma: An Outstanding Pediatric Case - Tommaso Alterio; Roberto Chimenz; Salvatore Arena; Giovanni Conti; Sabrina Cardile; Carmelo Romeo; Carmelo Salpietro; Carmelo Fede (Case Reports in Pediatrics)
We report a case of a 3-year-old North African child, initially assessed for nonspecific urinary symptoms such as haematuria and burning urination. The ultrasound evaluation showed a vegetating mass occupying the lumen with weak vascular signs at the Colour-Doppler evaluation. An explorative cystoscopy was performed and it revealed a nonbleeding lesion, white in colour, pedunculated, projecting into the lumen, and associated with a brown satellite formation. Histological examination showed a mixed Botryoid and Spindle Cell Rhabdomyosarcoma. This mixed histology has not been described before and no statistical data are reported in literature so far. Despite the Embryonal Rhabdomyosarcoma variant being the most common, the association characterized by two histological Rhabdomyosarcoma subtypes such as Botryoid and Spindle Cell is rarely observed and it is important to get an accurate histological diagnosis in order to immediately start the correct treatment protocol.